Analisis Dampak Lingkungan dan Sosial pada UMKM Menggunakan Metode Interpretive Structural Modeling - Hamzah, Dimas; Rizky Pratama, Bayu; Vanny Ravidianti, Nabilla; Yuliawati, Evi (Jurnal Teknik, 2025)
Small and Medium Enterprises (SMEs) in Indonesia make a significant contribution to the national economy, particularly in addressing poverty and unemployment. One su`ch SME in Mojokerto, which produces cassava crackers, faces various environmental and social issues in its production process. This study aims to analyze and classify these factors using the Interpretative Structural Modeling (ISM) method. The results of the ISM hierarchical structure analysis show that the factor "Employees parking vehicles haphazardly" is at level three, "Drying process obstructs public road access" is at level two, while "Unpleasant odor during drying," "Noise from machinery during production," and "Air pollution from the frying process" are at level one. The MICMAC diagram indicates that "Unpleasant odor during drying" and "Air pollution from the frying process" are the most critical factors and have the highest priority due to their significant influence on other elements.